Direct observation of spin correlations in an artificial triangular lattice Ising spin system with grazing-incidence small-angle neutron scattering. Issue 6 (7th May 2021) - Pip, Petai; Glavic, Artur; Skjærvø, Sandra Helen; Weber, Anja; Smerald, Andrew; Zhernenkov, Kirill; Leo, Naëmi; Mila, Frédéric; Philippe, Laetitia; Heyderman, Laura J.
Abstract : Short-range correlations in the highly frustrated spin-liquid state of an artificial triangular-lattice Ising spin system were measured using grazing incidence small-angle neutron scattering and quantified using an empirical structure factor. Abstract : The triangular lattice with Ising magnetic moments is an archetypical example of geometric frustration. In the case of dipolar-coupled out-of-plane moments, the geometric frustration results in a disordered classical spin-liquid state at higher temperatures while the system is predicted to transition to an anti-ferromagnetic stripe ground state at low temperatures. In this work we fabricate artificial triangular Ising spin systems without and with uniaxial in-plane compression to tune the nature and temperature of the correlations. We probe the energy scale and nature of magnetic correlations by grazing-incidence small-angle neutron scattering. In particular, we apply a newly-developed empirical structure-factor model to describe the measured short-range correlated spin-liquid state, and find good agreement with theoretical predictions. We demonstrate that grazing-incidence neutron scattering on our high-quality samples, in conjunction with detailed modeling of the scattering using the Distorted Wave Born Approximation, can be used to experimentally quantify the spin-liquid-like correlations in highly-frustrated artificial spin systems.